Agency costs of debt and monitoring - Mustapha, Mazlina; Che Ahmad, Ayoib (World Business Institute, 2011)
The purpose of this paper is to investigate how the debt structure of an organisation affects its demand and preference for monitoring costs in Malaysian business environment. Data is collected using primary and secondary sources. Multiple regression analysis is used. The findings indicate that debt structure have negative significant relationship with total monitoring costs. However the debt structure is not significant when the cost of directorship and auditing are compared. But when internal auditing and external auditing costs are compared, the result indicates that companies with high debt structure have significantly more external auditing costs. This result is consistent with prior studies and supports the notion that highly geared companies demand more external audit as the banks need the independent third party to verify the figures in the financial statements prepared by the management.